Rooting of shoot cuttings derived of root cuttings of blackberry - Dias, João Paulo Tadeu [UNESP]; Ono, Elizabeth Orika [UNESP]; Filho, Jaime Duarte (FapUNIFESP (SciELO), 2011)
This study aimed to evaluate the effect of indolyl-3-butyric acid (IBA) in promoting the rooting of blackberry shoots derived of root cuttings. This work was conducted from June to August 2010, at UNESP, Botucatu, Sao Paulo state, Brazil, under the randomized block design, with six concentrations of IBA and six replications of 12 shoot cuttings per plot. The treatments consisted of six concentrations of IBA, as a solution: T1= 0 mg L-1, T2= 250 mg L-1, T3= 500 mg L-1, T4= 1000 mg L-1, T5= 2000 mg L-1 and T6= 4000 mg L-1 applied on the basis of shoots cuttings for ten seconds. After 60 days, the percentage of rooting, the root fresh weight, the root dry weight, the length of root and the survival percentage, were evaluated. The concentration of 250 mg L-1 IBA favored characteristics as fresh and dry weight of roots originating from roots of blackberry. The highest concentrations of IBA inhibited root development and characteristics??? (please, verify the 'Resumo') of the shoots cuttings.
Enraizamento de Estacas de Brotações Oriundas de Estacas Radiculares de Amoreira-Preta
Keywords: Auxin; Cuttings; Multiplication; Rubus spp.